Prevalence of anemia in diabetes mellitus and chronic renal disease (Study of 100 patients) - Dr. Mohammed Adnan Khaleefah; Dr. Mohammed Kareem Ahmed; Dr. Mohamed ismael jawameer; Dr.Duraid khalil Ibrahim (Genius Journals, 2023)
prior to a substantial decrease in glomerular filtration rate (GFR), anemia is already a typical consequence of diabetic renal disease. Setting: Medical ward and outpatient clinic Hospital Subjects and Procedures: Hospital functioned as the study's outpatient clinic. From June 2017 to January 2019, the research team gathered data using a case series study approach. There were one hundred people who were patients. Seventy women (or 70%) and Thirty men (or 30%) participated in this study. Males make for 10% of the anemic population while females account for 20%. Diabetic individuals typically weighed in at a mean of 73.54 pounds (11.12 kg)
Keywords: Diabetic; Anemia; Renal Impairment